A study on personal selling and social media towards M7 Pro Oil user - Abbas, Suhaimi (2015)
The primary to conduct this study about how M7 team of Sabah to bring M7 Pro Oil product reach to consumers or end users through Push and Pull strategies of marketing channel. M7 Pro Oil is one of the main products from Mutiara Motors Sdn. Bhd. located at Larkin, Johor Baharu, whereby the main business is selling luxuries car then decided to spread their wings in products lines business. The M7 spread their wings to the Japan and USA namely M7Japan and M7USA. They forming a brand product namely M7 Drive which is M7 stands for car things such Oil engine (M7 Pro Oil), merchandises (Clothes, Keychain and so on) and, performance part (Exhaust, ECU and so on). The M7 brand name spread like a mushrooms in some countries which focus on car modification lover in terms of highly performance machine. The brand name was known in Japan and America since M7 technologies came from it and some other countries such German and France knowing it.